Global Communication: Paradox of Integration and Fragmentation (A Postcolonial Perspective) - Umar Suryadi Bakry (Greenation Research & Yayasan Global Resarch National, 2026)
This article analyzes the paradox of contemporary global communication from a post-colonial perspective, namely how communication technology and digital media simultaneously drive global integration while generating social, cultural, and political fragmentation. On the one hand, the internet, social media, and digital platforms expand cross-border connectivity, accelerate information exchange, and shape the global public sphere. On the other hand, the structure of global communication remains dominated by states and corporations from the Global North, thus reproducing colonial inequalities in a new form often referred to as digital colonialism. This research uses qualitative methods with a critical literature approach based on post-colonial theory, global communication, and the political economy of media. The results show that global integration does not occur neutrally but is shaped by power relations that determine who produces, distributes, and controls the flow of information. Fragmentation emerges through digital polarization, platform algorithms, media nationalism, and local cultural resistance to global homogenization. This article concludes that 21st-century global communication is an arena of contestation between integration and fragmentation, where colonial legacies continue to influence the structure of international communication. Therefore, a more inclusive, decolonial, and equitable global communication governance is needed.